Laser surface cleaning of 50CrMo4 steel - Lim, Daniel Yee Hui (2019)
Laser cleaning is a new and potential cleaning technique in the industries. Unfortunately, only a few studies have been done for laser cleaning on 50CrMo4 material. This project was initiated to analyse 50CrMo4 alloy steel sample with an effect of various scan speed and different scan times. The alloy steel samples were laser cleaned with Femtosecond (FS) laser. Scan speeds and number of scan times were varied, and the change in properties such as the surface profile, characteristics, and roughness before and after the laser ablation. To investigate and analyse the data, Scanning Electron Microscope Images were captured to see the surface characteristics, and surface roughness tests were conducted on the alloy steel by using TalyScan. After the experiment on the alloy steel, the effect of the scanning speeds and scan times affected the surface characteristics and the surface roughness. It was observed that at lower scanning speed, the surface gets deformed and the sides of the craters turned dark. The surface roughness (Sa) was found to increase with low scan speed. Therefore, with the observation and analysis on the samples under the effect of different scanning speed, the ideal parameter for the scan speed is 10mm/s. Also, it was observed that at higher number of scan times, the surface gets deformed into a crests and valley pattern which formed the crater in the laser irradiated region. The surface roughness (Sa) was found to increase with increasing number of scan times. As such, with the observation and analysis on the samples under the effect of different number of scan times scan times, the ideal parameter for scan times is between 1 to 5 times.